Hubungan Lama Menstruasi Dengan Kadar Hemoglobin Pada Mahasiswi Fakultas Kedokteran Universitas Palangka Raya - Karamo, Beatrice Benita; Kahanjak, Donna Novina; Praja, Rian Ka; Balyas, Abi Bakring; Trisia, Adelgrit (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Anemia is a non-communicable disease that is one of the main causes of insufficient iron reserves or a component that forms red blood cells or hemoglobin (Hb). One factor suspected to influence anemia is the duration of menstruation. This study aims to determine the relationship between the duration of menstruation and hemoglobin levels in female students of the Faculty of Medicine at Palangka Raya University from the 2020, 2021, and 2022 cohorts in the year 2023. The study was conducted on 74 female students selected through random sampling. Menstrual duration data were collected online in the form of a Google Form, and Hb level data were obtained directly from the Hb Test Meter MHD-1. This research is an Analytical Observational study with a Cross-Sectional approach that will be analyzed using the Spearman test. Respondents were aged 18-22 years, and out of 74 respondents, 72 respondents (97.3%) had a normal menstrual duration, while 2 respondents (2.7%) had an abnormal menstrual duration. In the examination of Hb levels, 46 respondents (62.2%) did not have anemia, while 28 respondents (37.8%) had anemia. Based on the results of the Spearman test, a p-value of 0.724 (p>0.05) was obtained, indicating that the hypothesis is rejected, and there is no relationship between the duration of menstruation and hemoglobin levels.